Seroprevalence and some demographic factors associated with Toxoplasma gondii infection among female population in Duhok province, Iraq - Salih, Janan Mohammed; Salih Mero, Wijdan Mohammed; Eassa, Souzan Hussein (International Journal of Research in Medical Sciences, 2020)
Background: The causative agent of toxoplasmosis is Toxoplasma gondii which is an intracellular protozoan. It has an important role in abortion and congenital diseases in pregnant women, which lead to infant’s defectiveness birth when pregnant, are exposed during pregnancy. Toxoplasmosis is one of the most prevalent and most successful parasitic infectious disease worldwide, due to its efficient transmission through the ingestion of tissue cysts in undercooked and infected meat, or the ingestion of oocysts in contaminated vegetables and water. The present study aimed to investigate the seroprevalence rate of anti-Toxoplasma gondii Abs and their relation to some demographic factors among females, in Duhok province/ Kurdistan Region/ Iraq. Methods: During the period from October 2016 to November 2017, a total of 792 random blood samples were collected from the female population of different ages (16-55) years and various socioeconomic classes, who attended Obstetrics and Gynecology Hospital, Azadi teaching hospital and Central Public Health Laboratory/ Duhok. Results: Out of 792 samples examined, 288 (36.3%) were seropositive from which 282 (35.61%) were found seropositive for IgG, while only six samples (0.76%) were seropositive for IgM. Regarding to occupation, the highest rate for chronic toxoplasmosis was reported in housewives followed by employed and students at rates of 40.19%, 22.3%, and 14.0%, respectively. These outcomes were statistically significant (p<0.05). The age group 36-45 years showed the highest seropositive rate for both IgG and IgM Abs which were 41.02% and 1.28%, respectively, which was statistically non-significant. The higher rate of seropositivity was observed among married females 39.93%, and pregnant 41.9% versus non-pregnant 33.3%. This difference was statistically significant (p<0.05) among married while non-significant in pregnant. Concerning to blood groups, the highest rate of seropositivity was reported among females with blood group AB+ which was 60% followed by group O- which was 46.7 %. This difference was statistically non-significant (p>0.05). Conclusions: This study showed the importance of demographic factors to the epidemiology of T. gondii in females, which support the role of public health in the control of infectious diseases.